Systolic and Diastolic Blood Pressure, Incident Cardiovascular Events and Death in Elderly Persons: The Role of Functional Limitation in the Cardiovascular Health Study - Peralta, Carmen A. (2014)
Whether limitation in ability to perform activities of daily living (ADL) or gait speed can identify elders in whom the association of systolic (SBP) and diastolic (DBP) blood pressure with cardiovascular events (CVD) and death differs is unclear. We evaluated whether limitation in ADL or gait speed modify the association of SBP or DBP with incident CVD (N= 2,358) and death (N=3,547) in the Cardiovascular Health Study. Mean age was 78 ± 5 and 21% reported limitation in ≥1 ADL. There were 778 CV events and 1,289 deaths over 9 years. Among persons without and with ADL limitation, SBP was associated with incident CVD: HR (per 10 mmHg increase) 1.08 (95% CI 1.03, 1.13) and 1.06 (0.97, 1.17), respectively. ADL modified the association of DBP with incident CVD. Among those without ADL limitation, DBP was weakly associated with incident CVD, HR 1.04 (0.79, 1.37) for DBP > 80, compared with <65 mmHg. Among those with ADL limitation, DBP was inversely associated with CVD: HR 0.65 (0.44, 0.96) for DBP 66–80 mmHg and HR 0.49 (0.25, 0.94) for DBP > 80, compared to DBP ≤ 65. Among persons with ADL limitation, a DBP 66–80 had the lowest risk for death, HR 0.72 (0.57, 0.91), compared with DBP ≤ 65. Associations did not vary by 15 feet walking speed ADL can identify elders in whom diastolic hypotension is associated with higher CV risk and death. Functional status, rather than chronologic age alone, should inform design of hypertension trials in elders.